Influence of Cutting Materials and Growth Regulators on the Growth of Trema (Trema orientalis L.) Cuttings - NFN Danu; Dede J. Sudrajat; Nurmawati Siregar (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Trema orientalis L. is a potential species to be developed as a biomass-based renewable energy source. The use of quality seedling that can be done through vegetative techniques is one of the issues that determine the success of plantation development. The purpose of this research is to get the best cutting material and an optimal growth regulator for multiplication of shoot cuttings. The shoot cuttings were obtained from 12-month-old seedlings. The design used was a complete randomized design (CRD) factorial pattern with two factors, namely cuttings positions (shoot, middle and bottom parts) and concentration of naphthalene acetic acid (NAA) growth regulator of 0, 50, 100, 150, 200, 250, and 300 ppm. The result showed that T. Orientalis propagation can be carried out well by using seedling shoot section soaked in NAA 300 ppm for 10 minutes. The treatment was able to have the percentage of rooting cutting of 71.67percent, number of roots of 6 pieces, root dry weight of 0.088 g, and shoot dry weight of 0.148 g.